Factors Affecting Consumer Purchase Intentions of Organic Products in Lalitpur District - Shrestha, Ranu Maiya (Pravaha, 2021)
This study aims to identify consumer buying behavior towards organic foods in the Lalitpur district. The specific objectives of this study are to study the awareness of consumer buying behavior toward organic foods and to identify the factors that affect consumer buying behavior toward the organic foods Nepalese market. The study used descriptive and inferential analysis based on primary data. The survey method is used as a closed-end questionnaire research method. Each variable is measured using 5-points Likert scales. Both descriptive and inferential analyzes were used as statistical tools for the analysis of the data collected. In this study 200 sample sizes have been used to analyze consumer buying behavior towards organic foods in Sunakothi, Thecho, Chapagau of Lalitpur district. The results indicate that consumers have a positive awareness of organic foods. Thus, it concluded that respondents' awareness level was good while buying organic foods. Based on the result, health-conscious, environment conscious, price, taste awareness are factors affecting consumer buying behavior towards organic foods. Consumer awareness level is quite well about organic foods. The majority of respondents were conscious of their health while buying organic foods. The majority of consumers feel that the prices of organic foods were high than conventional foods. This study concluded that the Nepalese market was aware of organic foods. The awareness level of consumers was quite goods.